Preeclampsia and Gestational Hypertension: Biochemical and Antioxidant Features in Vitro Might Help Understand Different Outcomes - Victoria Elizabeth Galvão; Ricardo Carvalho Cavalli; Valeria Cristina Sandrim (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2022)
Abstract Objective Gestational hypertension (GH) is characterized by increased blood pressure after the 20th gestational week; the presence of proteinuria and/or signs of end-organ damage indicate preeclampsia (PE). Heme oxygenase-1 (HO-1) is an antioxidant enzyme with an important role in maintaining endothelial function, and induction of HO-1 by certain molecules shows potential in attenuating the condition's effects over endothelial tissue. HO-1 production can also be stimulated by potassium iodide (KI). Therefore, we evaluated the effects of KI over HO-1 expression in human umbilical vein endothelial cells (HUVECs) incubated with plasma from women diagnosed with GH or PE. Methods Human umbilical vein endothelial cells were incubated with a pool of plasma of healthy pregnant women (n = 12), pregnant women diagnosed with GH (n = 10) or preeclamptic women (n = 11)with or without the addition of KI for 24 hours to evaluate its effect on this enzyme expression. Analysis of variance was performed followed by Dunnet's test for multiple comparisons between groups only or between groups with addition of KI (p ≤ 0.05). Results KI solution (1,000 µM) reduced HO-1 in the gestational hypertension group (p = 0.0018) and cytotoxicity in the preeclamptic group (p = 0.0143); treatment with KI reduced plasma cytotoxicity but did not affect the preeclamptic group's HO-1 expression. Conclusion Our findings suggest that KI alleviates oxidative stress leading to decreased HO-1 expression; plasma from preeclamptic women did not induce the enzyme's expression in HUVECs, and we hypothesize that this is possibly due to inhibitory post-transcriptional mechanisms in response to overexpression of this enzyme during early pregnancy.